Development and performance of a clear aligner film loaded with sustained release hydrogen peroxide gel - Cheng, Yuxun; Fang, Shishu; Liu, Xulin; Li, Xin; Song, Zhixin; Ma, Yanning; Jin, Zuolin (Frontiers in Materials, 2023)
Introduction: Clear aligner treatment (CAT) has become popular over recent years because it is both comfortable and aesthetically acceptable. However, most of patients undergoing orthodontic treatment request dental bleaching. Aim: This study was aimed to develop a thermoforming film loaded with hydrogen peroxide as a clear aligner and detect its efficiency on teeth blenching and its influence on shear bonding strength for attachment. Methods: The thermoforming film loaded with sodium alginate-dopamine/ Mesoporous silica nanoparticles compound gel was immersed in 6 wt% hydrogen peroxide solution and the hydrogen peroxide was loaded into mesoporous silica nanoparticle channels by capillary action. Six dentition models were prepared with 90 isolated human premolars and divided into the experiment group, the condition control group and the blank control group, respectively. Then, the experiment group wore the clear aligner made by the thermoforming film loaded with hydrogen peroxide for 40 days ; and the conditional control group wore the clear aligner made by the ordinary thermoforming film for 40 days. The aligners were updated every 10 days and the color of teeth was measured every 10 days. Changes in color parameters (L, a * and b *) and the shear bonding strength of attachment of isolated premolars were measured.results: Isolated premolars treated by bleaching experiments showed an increase in L value and a decrease in both a* and b* values. The shear bonding strength for attachment after bleaching was 22.78±2.28MPa, which had no significant change compared with the shear bonding strength for attachment without bleaching experiment (P> 0.05). Conclusion: A thermoforming film featuring the sustained release of hydrogen peroxide had a good bleaching effect on isolated teeth and had no significant influence on the shear bonding strength for attachment.